Evidence Mapping of Low Birth Weight and Stunting Association: A Holistic Scoping Review (2022–2024) - Ardiyanto, Muhammad Abim Aufarizqi; Setiawan, Komang Hendra; Pasek, Made Suadnyani (Syntax Literate, 2025)
Stunting and low birth weight (LBW) are significant public health challenges that have a global impact on infant development. It is imperative to comprehend the correlation between LBW defined as a birth weight below 2,500 grams and subsequent stunting in order to develop targeted interventions that enhance the health outcomes of children. The objective of this scoping review was to systematically map and integrate the findings regarding the association between stunting incidence in children under five and LBW, utilizing literature published between 2022 and 2024. We conducted a search of PubMed, Scopus, Google Scholar, and SciSpace from January 2022 to October 2024 in accordance with PRISMA-ScR guidelines. A particular emphasis was placed on Indonesian journals that were ranked Sinta. The criteria were satisfied by twenty-seven studies, which included meta-analyses, systematic reviews, case-control studies, facility base studies, and national surveys. Meta-analytic data indicated that the likelihood of stunting was 2.19-2.42 times higher in children who were underweight 2.19 to 2.42 (95% CI: 1.77-3.15).. National survey analyses from Bangladesh, India, and Zambia confirm this association with adjusted odds ratios between 1.19 and 3.24. Facility-based studies report even stronger associations (OR: 10.9, 95% CI: 5.85-20.30). The relation was consistently supported by Indonesian studies, with odds ratios ranging from 1.76 to 3.95. Integrated interventions addressing maternal nutrition, antenatal care quality, and early childhood nutrition are essential for breaking the cycle of intergenerational malnutrition.